The emerging role of extracellular vesicles in fungi: a double-edged sword - Lai, Yi; Jiang, Bowei; Hou, Fangpeng; Huang, Xinhong; Ling, Baodian; Lu, Hongfei; Zhong, Tianyu; Huang, Junyun (Frontiers in Microbiology, 2023)
Fungi are eukaryotic microorganisms found in nature, which can invade the human body and cause tissue damage, inflammatory reactions, organ dysfunctions, and diseases. These diseases can severely damage the patient's body systems and functions, leading to a range of clinical symptoms that can be life-threatening. As the incidence of invasive fungal infections has progressively increased in the recent years, a wealth of evidence has confirmed the "double-edged sword" role of fungal extracellular vesicles (EVs) in intercellular communication and pathogen-host interactions. Fungal EVs act as mediators of cellular communication, affecting fungal-host cell interactions, delivering virulence factors, and promoting infection. Fungal EVs can also have an induced protective effect, affecting fungal growth and stimulating adaptive immune responses. By integrating recent studies, we discuss the role of EVs in fungi, providing strong theoretical support for the early prevention and treatment of invasive fungal infections. Finally, we highlight the feasibility of using fungal EVs as drug carriers and in vaccine development.